Quality standards for bone conduction implants. (2nd December 2015) - Gavilan, Javier; Adunka, Oliver; Agrawal, Sumit; Atlas, Marcus; Baumgartner, Wolf-Dieter; Brill, Stefan; Bruce, Iain; Buchman, Craig; Caversaccio, Marco; De Bodt, Marc T.; Dillon, Meg; Godey, Benoit; et al.
Abstract: Conclusion: Bone conduction implants are useful in patients with conductive and mixed hearing loss for whom conventional surgery or hearing aids are no longer an option. They may also be used in patients affected by single-sided deafness. Objectives: To establish a consensus on the quality standards required for centers willing to create a bone conduction implant program. Method: To ensure a consistently high level of service and to provide patients with the best possible solution the members of the HEARRING network have established a set of quality standards for bone conduction implants. These standards constitute a realistic minimum attainable by all implant clinics and should be employed alongside current best practice guidelines. Results: Fifteen items are thoroughly analyzed. They include team structure, accommodation and clinical facilities, selection criteria, evaluation process, complete preoperative and surgical information, postoperative fitting and assessment, follow-up, device failure, clinical management, transfer of care and patient complaints.